Intergenerational Social Change and The Digital Transformation of Fatherhood. - Çakır, Hülya; Gedik, Esra (Electronic Turkish Studies, 2026)
As the family—long positioned at the core of social organization—evolves across generations, fatherhood is being redefined both in normative expectations and in everyday care giving practices. With the transformation of the family institution, fatherhood is evolving from a traditional role reduced to mere economic responsibilities into a multifaceted experience encompassing emotional labor, caregiving, and coparenting practices. This study examines how intergenerational social change reshapes understandings of fatherhood in tandem with the digitization of care and visibility. Designed as a qualitative inquiry, there search employs semi-structured, in-depth interviews with fathers selected through maximum variations ampling across age cohorts, socio-economic locations and family configurations. Interview narrative sprobe how fathers make sense of and perform fatherhood, where continuities and breaks appear between generations, and which opportunities (e.g., the visibility of involved fatherhood, co-parenting coordination) and tensions (e.g., privacyconcerns, feminizing/"effeminate" labeling, technoference) emerge in digital contexts. This study aims to examine the transformation of fatherhood in the digital age within the context of intergenerational social change dynamics. The evolution of social structure and family relationships over time is also reshaping individual parenting roles. It offers the opportunity t oevaluate the impact of digitalization on fatherhood practices within the context of the transformation of traditional masculine norms. Data were analyze during the maticanalysis, demonstrating that fathering is co-constituted by socio-cultural context, generational effects and platform logics. The study contributes to debates on the digital transformation of fatherhood in Türkiye and generate simplications for father-focused support programs and digital parenting guidance.